Estética e cibercultura: arte no contexto da segregação dromocrática avançada - Trivinho, Eugênio (2006)
The essay puts in to context and problematizes, not without provocative intention, the relation between aesthetics and virtual supports in the above mentioned socio-historical outline-the one from the nineties on -, prioritising the technological and artistic premises, contradictions, paradoxes and horizons involved. From the dissection of cyberculture's modus operandi (articulated by a worldwide dromocratic neodarwinism) and from the criticism of intemational aesthetic cybercelebration (which involuntarily and indirectly involves art in the social segregation based on the widespread use of information technology and interactivity), the text provides, as a contribution to the debate, new conceptual indicators for the understanding of the redefmition that the 'statute' and the cultural role of the state-of-theart artistic production has undergone in the contemporary context.